2010
DOI: 10.1002/jmv.21732
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) prevalence and type distribution, and HPV‐associated cytological abnormalities in anal specimens from men infected with HIV who have sex with men

Abstract: Human papillomavirus (HPV) detection and typing using the PapilloCheck test and cytological examination were carried out in anal samples collected from 67 men seropositive for human immunodeficiency virus (HIV) who have sex with men. Fifty (74.6%) patients had anal HPV infection, 46 (68.7%) had high-risk (HR) HPV infection, and 38 (56.7%) had multiple infection involving 2-9 (median, 3) HPV types. The HPV types identified most frequently were HPV 44/55 (19.4%), HPV 53 (19.4%), HPV 16 (16.4%), HPV 39 (16.4%), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 35 publications
12
31
0
Order By: Relevance
“…We have also found a high prevalence of abnormal anal cytologies (just over half), which is also consistent with previously reported data in HIV-infected MSM in Europe, the United States, and Canada, as well the prevalences of L-SIL and H-SIL that we have found of 38.1% and 4.6%, respectively (4,9,17,18,22,23). Indeed, in a recent publication from our group, González et al (9) described a high prevalence of anal SIL and a 7-fold-increased risk of anal SIL in MSM with five or more detectable HR-HPV types.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We have also found a high prevalence of abnormal anal cytologies (just over half), which is also consistent with previously reported data in HIV-infected MSM in Europe, the United States, and Canada, as well the prevalences of L-SIL and H-SIL that we have found of 38.1% and 4.6%, respectively (4,9,17,18,22,23). Indeed, in a recent publication from our group, González et al (9) described a high prevalence of anal SIL and a 7-fold-increased risk of anal SIL in MSM with five or more detectable HR-HPV types.…”
Section: Discussionsupporting
confidence: 93%
“…Salit et al (16), in 401 HIV-positive MSM in Canada, Conley et al (17), in 379 MSM from four U.S. cities, and Sahasrabuddhe et al (8), in 363 MSM from San Francisco, obtained prevalence values for any HPV type of 93%, 88.7%, and 94.4%, respectively, and HR-HPV prevalences of 88%, 88.7%, and 75.4%, respectively (8,16,17). Consistent with previous reports conducted in Europe, the United States, Australia, and Canada, in the present study, the prevalences of multiple HR-HPV infections and infections with more than four HPV types or more than four HR-HPV types are high (1,6,8,9,(16)(17)(18)(19). HPV16, as expected, was the most common HR-HPV type detected, with a prevalence of 34.7%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Yamada et al demonstrated that not high-copy number of HIV amount but current lower CD4-positive T cells is associated with higher grade cervical lesions in Kenyan women who had no ART [29].Wilkin et al reported that there was no association of current CD4-positive T cells and nadir CD4-positive T cells with abnormal anal cytology or high grade AIN [30]. Another previous study also found that HPV-DNA detection as well as cytological abnormalities were associated neither with HIV RNA detection in plasma nor with CD4-positive T cells [31]. Therefore, further studies, including large population samples and of longitudinal design, are required to clarify the risk factors associated with cytological abnormality by HPV infection among HIV-positive population.…”
Section: Discussionmentioning
confidence: 97%
“…This kit can determine 37 HPV genotypes, consisting of 15 high-risk HPV types (16,18,31,33,35,39,45, 51, 52, 56, 58, 59, 68, 73, 82), 10 low-risk HPV types (6,11,42,43,44,54,61,70,72,81), and 12 unknown-risk types (26,34,40,53,55,57,66,67,69,71,83,84), by flow-through hybridization and gene-chip methods using HPV-DNA amplified by PCR [17,19].…”
Section: Hpv-dna Test and Genotypingmentioning
confidence: 99%